Coastal identities in the modern age : on diversity of ethnic articulation in Storfjord, North Norway - Kim, Jung Im (Universitetet i Tromsø, 2010)
This thesis discusses Coastal identities in the modern age - the case of Storfjord in Northern Norway as studied in 2009. Populations in the coastal areas of Northern Norway are more or less a mixture of Coastal Sami, Kven and Norwegian. Historically, it might be analyzed as some results of the encounters of three ethnic groups; the Coastal Sami, Kven and Norwegian historically. Therefore, there is a natural tendency to choose a “both–and” ethnicity. However, the Coastal Sami and Kven experienced the worst form of the Norwegianization policy until the last century. The Coastal Sami and Kven ethnicity were often stereotyped as a stigmatized ethnic identity or just inferior. The mixed ethnic population in Northern Norway was therefore integrated into the Norwegian mainstream. My thesis brings out the contemporary changes among them. I observed the different ethnic identifications among the mixed population in Storfjord. I analyzed them in three categories: Category 1 termed “the North Calotte Cocktail” and “Northerner (Nordlending in Norwegian)” group. Category 2 is the group who chose the single ethnic identity as Sami instead of Northern Norwegian. Category 3 comprises of those who claim double/multiple ethnicity instead of Northern Norwegian. Furthermore, this thesis includes how these different ethnic identifications are influencing Sami ethnic revitalization and their mechanisms for strengthening their new identity.